Potential Use of Essential Oil Isolated from Cleistocalyx operculatus Leaves as a Topical Dermatological Agent for Treatment of Burn Wound - Gia-Buu Tran; Nghia-Thu Tram Le; Sao-Mai Dam (Hindawi Limited, 2018)
Several herbal remedies have been used as topical agents to cure burn wound, one of the most common injuries in worldwide. In this study, we investigated the potential use of Cleistocalyx operculatus essential oil to treat the burn wound. We identified a total of 13 bioactive compounds of essential oil, several of which exhibited the anti-inflammatory and antimicrobial activities. Furthermore, the essential oil showed the antibacterial effect against S. aureus but not with P. aeruginosa. The supportive effect of essential oil on burn wound healing process also has been proven. Among three groups of mice, wound contraction rate of essential oil treated group (100%) was significantly higher than tamanu oil treated (79%) and control mice (71%) after 20 days (0.22±0.03 versus 0.31±0.02 cm2, resp., p<0.05). Histological studies revealed that burn wounds treated with essential oil formed a complete epidermal structure, thick and neatly arranged fibers, and scattered immune cells in burn wound. On the contrary, saline treated burn wound formed uneven epidermal layer with necrotic ulcer, infiltration of immune cells, and existence of granulation tissue. This finding demonstrated Cleistocalyx operculatus essential oil as promising topical dermatological agent to treat burn wound.